ENSO-related variation of equatorial MRG and Rossby waves and forcing from higher latitudes - Yang,G-Y; Hoskins,BJ (Quarterly Journal of the Royal Meteorological Society, 2016)
The contrasting behaviour of westward-moving mixed Rossby–gravity (WMRG) and the first Rossby (R1) waves in El Niño (EN) and La Niña (LN) seasons is documented with a focus on the Northern Hemisphere winter. The eastward-moving variance in the upper troposphere is dominated by WMRG and R1 structures that appear to be Doppler-shifted by the flow and are referred to as WMRG-E and R1-E. In the east Pacific and Atlantic the years with stronger equatorial westerly winds, LN in the former and EN in the latter, have the stronger WMRG and WMRG-E. In the east Pacific, R1 is also a maximum in LN. However, R1-E exhibits an eastward shift between LN and EN.The changes with El Niño/Southern Oscillation (ENSO) phase provide a test bed for the understanding of these waves. In the east Pacific and Atlantic, the stronger WMRG-E and WMRG with stronger westerlies are in accord with the dispersion relation with simple Doppler-shifting by the zonal flow. The possible existence of free waves can also explain stronger R1 in EN in the Eastern Hemisphere. 1-D free-wave propagation theory based on wave activity conservation is also important for R1. However, this theory is unable to explain the amplitude maxima for other waves observed in the strong equatorial westerly regions in the Western Hemisphere, and certainly not their ENSO-related variation. The forcing of equatorial waves by higher-latitude wave activity and its variation with ENSO phase is therefore examined. Propagation of extratropical eastward-moving Rossby wave activity through the westerly ducts into the equatorial region where it triggers WMRG-E is favoured in the stronger westerlies, in LN in the east Pacific and EN in the Atlantic. It is also found that WMRG is forced by Southern Hemisphere westward-moving wave trains arching into the equatorial region where they are reflected. The most significant mechanism for both R1 and R1-E appears to be lateral forcing by subtropical wave trains.